Exodus! Large-scale displacement and social adjustments of resident Atlantic spotted dolphins (Stenella frontalis) in the Bahamas. - Denise L Herzing; Bethany N Augliere; Cindy R Elliser; Michelle L Green; Adam A Pack (PLoS ONE)
Over the last 20 years, significant habitat shifts have been documented in some populations of cetaceans. On Little Bahama Bank (LBB) there are sympatric communities of resident Atlantic spotted dolphins (Stenella frontalis) and bottlenose dolphins (Tursiops truncatus), monitored since 1985. The size and social structure (three clusters: Northern, Central, Southern) have been stable among the spotted dolphin community with little immigration/emigration, even after large demographic losses (36%) following two major hurricanes in 2004. In 2013 an unprecedented exodus of over 50% (52 individuals) of the spotted dolphin community was documented. The entire Central cluster and a few Northern and Southern individuals relocated 161 km south to Great Bahama Bank (GBB), also home to two sympatric resident communities of spotted dolphins and bottlenose dolphins. During the late summer of 2013 and the summers of 2014 and 2015 both sites were regularly monitored but no former LBB dolphins returned to LBB. Uncharacteristic matriline splits were observed. Social analyses revealed random associations for those spotted dolphins and very little integration between spotted dolphins that moved to GBB (MGBB) and those dolphin resident to GBB (RGBB). Male alliances among spotted dolphins were present, with some altered patterns. On LBB, the operational sex ratio (OSR) was reduced (.40 to .25). OSR for MGBB and RGBB dolphins were similar (.45 and .43). A significant steady decrease in sea surface temperature and chlorophyll a (a proxy for plankton production) occurred on LBB leading up to this exodus. Similar trends were not present over the same period on GBB. The sudden large-scale shift of spotted dolphins from LBB to GBB in association with the gradual decline in certain environmental factors suggests that a possible "tipping point" was reached in prey availability. This study provides a unique view into social and genetic implications of large-scale displacement of stable dolphin communities.